The attitudes of students towards the use of ICT during their studies - Stošić, Lazar; Fadiya, Samson O. (Rossijskij psihologičeskij žurnal., 2018)
The purpose of this study was to examine attitudes of students towards the use of ICT during their studies. The survey included 285 students from Girne American University, Turkey. The sample consists of the students from first to fourth grade. The scale consists of 45 claims and is intended for determining students’ attitudes towards the use of ICT during their studies. Questionnaires were utilized to gather information on the attitudes of students towards the use of ICT during their studies. Information was broke down using SPSS statistical package (IBM SPS Statistics Version 20) and with Monte Carlo program for the parallel examination. The study established that students towards the utilization of ICT made the significant commitment to the students' academic performance. It is advanced that the discoveries of this study will be valuable to students to acquire knowledge into the ICT variables that influence students' scholastic execution and consequently enhance their academic performance.Results indicate that after one year of the intervention, there were statistically significant differences between the two groups only in sight vocabulary (at kindergarten and grade 1) and in alphabet (kindergarten). In all other areas of language development, there were no statistically significant differences between the achievement scores of the two groups. Results show that students appear to react to the prerequisites of their courses, programs, and universities. In all cases, there is a reasonable relationship between the students' view of handiness on certain ICT assets the critical quantities of understudies are quick to see ICT misused in the educating and learning process. There is positively scope for further research to examine how ICT interfaces crosswise over various areas and how the cross-connection application impacts its utilization. The purpose of this study was to examine attitudes of students towards the use of ICT during their studies. The survey included 285 students from Girne American University, Turkey. The sample consists of the students from first to fourth grade. The scale consists of 45 claims and is intended for determining students’ attitudes towards the use of ICT during their studies. Questionnaires were utilized to gather information on the attitudes of students towards the use of ICT during their studies. Information was broke down using SPSS statistical package (IBM SPS Statistics Version 20) and with Monte Carlo program for the parallel examination. The study established that students towards the utilization of ICT made the significant commitment to the students' academic performance. It is advanced that the discoveries of this study will be valuable to students to acquire knowledge into the ICT variables that influence students' scholastic execution and consequently enhance their academic performance.Results indicate that after one year of the intervention, there were statistically significant differences between the two groups only in sight vocabulary (at kindergarten and grade 1) and in alphabet (kindergarten). In all other areas of language development, there were no statistically significant differences between the achievement scores of the two groups. Results show that students appear to react to the prerequisites of their courses, programs, and universities. In all cases, there is a reasonable relationship between the students' view of handiness on certain ICT assets the critical quantities of understudies are quick to see ICT misused in the educating and learning process. There is positively scope for further research to examine how ICT interfaces crosswise over various areas and how the cross-connection application impacts its utilization.